Historical Study: Conceptual Study Of The Origin Of The Muslim Community In Pegayaman Village, Sukasada District, Buleleng Regency, Bali - Raisyabilla, Rangga Octava; Alhail, Hadi; Musthafa, Akram; Tricahya, Krishna; Utama, I Gusti Agung Gede Aditya; Sasea, Sanita Carolina; Afifi, Wayan M Aziz; Putri, Adesti Anggita (Program Magister Pendidikan Sejarah FISH UNJ, 2025)
Historical Study of Pegayaman Village, Buleleng, Bali This journal examines the origin of Pegayaman Village, Buleleng, Bali, through a conceptual study of its history. This research is motivated by the lack of conceptual understanding of village history for the younger generation and the need for regeneration of local historians. The exploratory qualitative research method was applied with a focus on Banjar Dinas Barat Jalan, Pegayaman Village. Primary data was obtained through interviews and direct observations, while secondary data was obtained through observation and interviews with the main source. The results of the study show that the origin of Pegayaman Village is divided into 5 phases: 1. Threat and Conflict Phase: Pegayaman Village became a fortress for the defense of the Buleleng Kingdom from the attacks of the southern kingdom. 2. Recruitment Phase of 100 Muslim Laskar Blambangan: The Kingdom of Buleleng received the assistance of 100 Muslim Laskar from Blambangan to guard its territory. 3. Appreciation Phase with the Handover of Gatep Forest: Muslim soldiers were given gatep forest land as a form of appreciation for their services. 4. Phase of Naming the Area into Pegayaman Village: The name